2021
DOI: 10.1111/ajgw.12528
|View full text |Cite
|
Sign up to set email alerts
|

Timing of auxin treatment affects grape berry growth, ripening timing and the synchronicity of sugar accumulation

Abstract: Background and Aims: Climate change has resulted in earlier berry development and compressed harvests creating problems with harvesting and winery logistics and causing undesired modifications to grape and wine composition, such as elevated concentration of berry sugar and wine alcohol. Auxin treatment of grapevine bunches prior to veraison can counteract these adverse changes by delaying berry maturation. The most efficacious timing of 1-naphthaleneacetic acid (NAA) application along with the effects of appli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 29 publications
1
10
0
Order By: Relevance
“…The onset of grape ripening is triggered by the elevation of ABA and the decline of auxin . Previous studies have widely reported that prevéraison NAA application can delay the véraison and ripening of grapes. , ,, Our findings further demonstrated the inhibitory effect of NAA on grape ripening. Except for the delay in TSS accumulation, other parameters, such as pH value increase and TA decrease, were also observed to be delayed (as depicted in Figure ).…”
Section: Discussionsupporting
confidence: 74%
See 2 more Smart Citations
“…The onset of grape ripening is triggered by the elevation of ABA and the decline of auxin . Previous studies have widely reported that prevéraison NAA application can delay the véraison and ripening of grapes. , ,, Our findings further demonstrated the inhibitory effect of NAA on grape ripening. Except for the delay in TSS accumulation, other parameters, such as pH value increase and TA decrease, were also observed to be delayed (as depicted in Figure ).…”
Section: Discussionsupporting
confidence: 74%
“…Davis et al observed that 16 days of preveŕaison NAA treatment (50 mg/L) resulted in the significantly higher concentration of β-damascenone in "Cabernet Sauvignon" wines than control wines. 18 He et al found that NAA (100 mg/L) application at 14 days preveŕaison increased the concentrations of most norisoprenoid compounds in the grapes E-L 38. 9 These results suggested that the synthetic auxin has a positive impact on the production of β-damascenone in harvested grapes.…”
Section: ■ Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…It has been shown that IAA promotes plant growth at low concentrations, whereas conversely, high concentrations of IAA inhibit plant growth (Zafar et al, 2020). Furthermore, auxin application to grapevines prior to veraison delayed berry maturation, including sugar accumulation (Davies et al, 2022). Both melatonin and IAA are synthesized from tryptophan and have similar structures (Harderland, 2016;Zafar et al, 2020;Jahn et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…ABA is primarily catabolized to 8′-hydroxy ABA by ABA 8′-hydroxylase, which is encoded by the CYP707A gene and then isomerized to phaseic acid (PA) (Saito et al, 2004). It has been shown that auxin treatments, such as 1-naphthaleneacetic acid (NAA) treatment, delays maturation in grapes; however, the effect depends on the timing of treatment (Davies et al, 2022).…”
Section: Introductionmentioning
confidence: 99%